2006
DOI: 10.1590/s0103-84782006000200055
|View full text |Cite
|
Sign up to set email alerts
|

Composição do suco de uva caseiro de diferentes cultivares

Abstract: RESUMO Um volume considerável de uva do grupo das americanas da Serra Gaúcha é destinado para a produção de suco de uva caseiro. O objetivo do presente trabalho foi avaliar o efeito das cultivares Isabel, Bordô (Ives)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
2
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 0 publications
3
29
2
12
Order By: Relevance
“…In general there is great homogeneity in the density values, for which the lowest average for purple grape juices was 1.060 in 2015 and 2016 and the highest was 1.066 in the years 2012 to 2014, while the lowest average observed in white grape juices was 1.060 in 2014 and 2016 and the highest was 1.068 in 2012. Rizzon and Link (2006) [18] analyzed homemade purple grape juices from different varieties and obtained density results on average of 1.055 which are lower than this study's results. Rizzon and Miele (2012) [19] evaluated commercial juices of three types (whole, sweetened and reprocessed), for which average density values were respectively, 1.069, 1.070 and 1.061, showing numbers very compatible with the present work.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…In general there is great homogeneity in the density values, for which the lowest average for purple grape juices was 1.060 in 2015 and 2016 and the highest was 1.066 in the years 2012 to 2014, while the lowest average observed in white grape juices was 1.060 in 2014 and 2016 and the highest was 1.068 in 2012. Rizzon and Link (2006) [18] analyzed homemade purple grape juices from different varieties and obtained density results on average of 1.055 which are lower than this study's results. Rizzon and Miele (2012) [19] evaluated commercial juices of three types (whole, sweetened and reprocessed), for which average density values were respectively, 1.069, 1.070 and 1.061, showing numbers very compatible with the present work.…”
Section: Resultscontrasting
confidence: 87%
“…Several methodologies are used to produce grape juice, a common one involves the following steps: destemming and crushing, heating, addition of enzymes, juice extraction, clarification, pasteurization and bottling [6,7]. In the processing of white grape juices, some producers remove the peels before heating, which is not done with purple juices.…”
Section: Introductionmentioning
confidence: 99%
“…It is a non-fermented, non-alcoholic drink, with characteristic colour (red, white, rose), aroma (characteristic of the grape variety that gave rise to the juice) and taste [1]. Grapes are one of the earliest fruits used in the human diet and grape juices have become an economical alternative for grape producing regions [2].…”
Section: General Introductionmentioning
confidence: 99%
“…Freitas (2006) obtained 0.85% of acidity in grape juice of the same variety. Rizzon and Link (2006) found acidity varies due to the varieties characteristics and, studying grape juice from different cultivars, higher values of acidity for Isabel and Cabernet cultivars and lower values for Claret and Concord cultivars were obtained. Nagatto et al (2003) found values between 0.5 and 0.9% acidity in grape juice from Isabel cultivar.…”
Section: Resultsmentioning
confidence: 93%
“…This value is below the minimum recommended by the Brazilian legislation for grape juice, which is 14% (Brasil, 2000). Rizzon and Link (2006), studying the composition of homemade juice from different cultivars (Isabel, Claret, Concord and Cabernet Sauvignon) also found soluble solids under the law, with values between 12.2 and 13.1 ºBrix. According to Freitas (2006) andRizzonand Link (2006), these variations may occur probably due to the dilution effect of the water steam used in the heating and extraction of the pigments of grape due to the type of equipment and the conditions used.…”
Section: Resultsmentioning
confidence: 94%